PRODUÇÃO DE MUDAS DE PIMENTEIRA SUBMETIDAS AO FORNECIMENTO DE BIOESTIMULANTE VIA SEMENTE E FOLIAR - BARBOSA, M. S.; GUERRA, M. S.; DIAS, B. B; BINOTTI, F. F. S.; VIEIRA, G. H. C. (ANAIS DO ENIC, 2016)
-